Journal of Clinical and Translational Pathology 2021
DOI: 10.14218/jctp.2021.00009
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Changes of Adult Mitral Valves after Failed CorMatrix ECM Repair

Abstract: Background and objectives: CorMatrix acts as a tissue scaffold and is intended to promote the proliferation of small vessels and tissue remodeling to replicate normal tissue function. Methods:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…While in preclinical studies, SIS-ECM has shown very encouraging results ( Badylak et al, 1989 ; Lantz et al, 1992 ; Fallon, 2011; Padalino et al, 2012 ; Baker, 2018), the application of CorMatrix® in the clinic has not produced the same results. Immune reactions, inflammatory processes with the thickening of the patch, and finally calcifications in the surrounding tissue, were present in almost all cases considered (Woo, 2015; Nelson et al, 2016 ; Chakraborty 2021 ; Sood et al, 2021 ). To achieve our goal, we compared two decellularization protocols: the first based on the use of Triton X 100, as a non-ionic detergent and the second with its substitute, Tergitol 15 S 9.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While in preclinical studies, SIS-ECM has shown very encouraging results ( Badylak et al, 1989 ; Lantz et al, 1992 ; Fallon, 2011; Padalino et al, 2012 ; Baker, 2018), the application of CorMatrix® in the clinic has not produced the same results. Immune reactions, inflammatory processes with the thickening of the patch, and finally calcifications in the surrounding tissue, were present in almost all cases considered (Woo, 2015; Nelson et al, 2016 ; Chakraborty 2021 ; Sood et al, 2021 ). To achieve our goal, we compared two decellularization protocols: the first based on the use of Triton X 100, as a non-ionic detergent and the second with its substitute, Tergitol 15 S 9.…”
Section: Discussionmentioning
confidence: 94%
“…Immune reactions, inflammatory processes with the thickening of the patch, and finally calcifications in the surrounding tissue, were present in almost all cases considered (Woo, 2015;Nelson et al, 2016;Chakraborty 2021;Sood et al, 2021). To achieve our goal, we compared two decellularization protocols: the first based on the use of Triton X 100, as a non-ionic detergent and the second with its substitute, Tergitol 15 S 9.…”
Section: Discussionmentioning
confidence: 99%